Genetic Location of a Mutant of Bacteriophage T4 Deficient in the Ability to Induce Endonuclease II - Ray, Purnima (1972)
Reciprocal three-factor crosses and the use of a partial revertant of a putative ribonucleotide reductase mutant of Escherichia coli B/5 as indicator have made it possible to map denA (deficient in endonuclease II) between nrd-11 (ribonucleotide reductase gene B) and amM69 (gene 63) on the bacteriophage T4 chromosome.